Review of Richard Seymour’s The Twittering Machine - Phelan S (Massey University)
In his most explicitly philosophical book Pascalian Meditations, Pierre Bourdieu (2000) clarified what he meant by the notion of symbolic violence. Symbolic violence signifies more than simply forms of discursive power that mediate social relationships without the imposition of physical force. Rather, it signifies a form of violence that the target of the violence is themselves complicit in. “Symbolic power is exerted only with the collaboration of those who undergo it because they help to construct it as such” (p. 171).